Is it possible to follow-up the efficacy of vitamin D treatment by phalangeal radiographic absorpsiometry? [Araştirma yazisi D vi̇tami̇ni̇ tedavi̇si̇ni̇ n etki̇nli̇ǧi̇ falangeal radyogfrafi̇k absorpsi̇yometri̇ i̇le i̇zlenebi̇li̇r mi̇?] - (:unkn) unknown (My University, 2009)
Aim: Radiographic absorptiometry (RA) is a cheap and easily applicable technique for measuring bone mineral density (BMD) of the medium phalanges of fingers 2, 3 and 4. In this trial with elderly patients suffering from vitamin D deficiency, the aim is to investigate whether it is possible to follow short-term vitamin D treatment with phalangeal RA or not and to compare the consistency of measurement results with dual energy x-ray absorptiometry (DXA). Materials and Methods: Fifty-seven patients over 65 years old who had been determined as vitamin D deficiency (<50nmol/l) were included in this trial. Thirty patients received 1 μg of alphacalcidol and 500 mg elemenatry calcium once a day and the control group received 500 mg elementary calcium. Hand phalangeal, lumbar spinal and hip BMD measurements of all patients were performed at the beginning and the 6th month of the treatment. The consistency of percentage change of serum levels of vitamin D with RA and DXA results were statistically compared. Results: Baseline DXA BMD measurements of all of the patients were consistent with the RA measurement values. After 6 months of alphacalcidol and elementary calcium treatment, the difference in the levels of vitamin D was not statistically relevant, neither with DXA nor with RA. Conclusion: Although phalangeal radiographic absorptiometry is a reliable and practical method, its use in the short term follow-up of vitamin D treatment is thought to be limited.
Keywords: Dual energy x-ray absorptiometry (DXA); Phalangeal radiographic absorptiometry (RA); Vitamin D